Kemampuan Mengkonstruksi Bukti Geometri Mahasiswa Calon Guru Matematika Pada Perkuliahan Geometri - Samsul Maarif; Wahyudin Wahyudin; Fitri Alyani; Trisna Roy Pradipta (Universitas Hamzanwadi, 2020)
This study aims to analyze and describe the ability to construct proofs of perspective teacher mathematics students in basic geometrical lectures on the concepts of alignment, triangles, and concordance of two triangles. This research uses a descriptive qualitative method involving 35 prospective mathematics students at the Universitas PGRI Semarang. This study uses a qualitative descriptive method involving 35 students. The results of this study show that: (1) 28% of students sketched diagrams and used geometric labels appropriately on the constructed evidence; (2) 28.57% of students have the correct initial step of proof; (3) 28.57% of students can determine the exact conjecture that leads to the correct proof; (4) 25.71% of students are correct in compiling proof arguments by the correct postulate and theorem; (5) 25.71% of the thought flow process used by coherent students leads to valid evidence; and (6) 22.86% of students mastered theorems and concepts used in compiling constructing proof.